Fe-based amorphous coating for corrosion protection of magnesium alloy. (15th October 2016) - Guo, S.F.; Pan, F.S.; Zhang, H.J.; Zhang, D.F.; Wang, J.F.; Miao, J.; Su, C.; Zhang, C.
Abstract: In this work, AZ61 magnesium alloy coated with NiCrAl intermediate layer with outer of Fe-based amorphous coating was fabricated by high-velocity oxy-fuel thermally spraying. Through the intermediate metallic coating, the traditional mismatch of Fe-based materials and magnesium substrate was overcome, exhibiting good metallurgical bonding in the interface regions. The protective magnesium alloy with Fe-based amorphous coating possesses very high hardness and excellent corrosion resistance in 3.5% NaCl solution, demonstrating by nearly ten times of hardness higher and two orders of magnitude of corrosion rate lower than the magnesium substrate. Similarly to 316L stainless steel coatings, the current Fe-based amorphous coating with a very large passive region, shows much more positive of corrosion potential and much less corrosion current density than that of sprayed Al alloy coating and ceramic coatings on magnesium alloys previously reported. The outstanding feature of the protective magnesium alloy with amorphous coating can be attributed to its unique disorder structure and uniform chemical composition, which allows a very dense passivation film formed and uniform corrosion occurred. Our findings demonstrate that Fe-based amorphous coating is a promising candidate for protecting magnesium alloys with desirable corrosion resistance for structural/functional applications. Graphical abstract: The corrosion potential E corr of present Fe-based amorphous coating is much more positive than that of Al alloyed coatings, ceramic coatings and conversion coatings in 3.5% NaCl previously reported. Meanwhile, the corrosion current density i corr of Fe-based amorphous coating is much less than that of Al alloyed coatings and ceramic coatings. It should be noted that the present Fe-based amorphous coating, like 316L coating on magnesium alloys, exhibits a very broad passive region, indicating that the dense passive film on Fe-based amorphous coating surface has excellent corrosion resistance. Highlights: Fe-based amorphous coating was fabricated by HVOF on AZ61 magnesium alloy. The hardness of Fe-based amorphous coating was about ten times higher than that of matrix. The corrosion rate of the coated alloy was nearly two orders of magnitude lower than that of AZ61 alloy.